2011 IEEE PES Conference on Innovative Smart Grid Technologies - Middle East 2011
DOI: 10.1109/isgt-mideast.2011.6220820
|View full text |Cite
|
Sign up to set email alerts
|

Optimal placement of synchronized phasor measurement units based on differential evolution algorithm

Abstract: This paper proposes a method based on differential evolution (DE) algorithm for the problem of optimal placement of phasor measurement units (PMUs) in an electric power network. The problem is to minimize the required number of PMUs and, at the same time, maximize the PMU measurement redundancy subject to the constraint of achieving full network observability. Network observability is assessed with the aid of the topological observability rules. In order to cope with the continuous changes in the power system'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…In (17), w3 and w4 are two weight values. The parameter NL refers to the number of buses that are not being observed twice by the PMUs placement and S is the measurement redundancy used when considering the single PMU loss.…”
Section: Single Pmu Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…In (17), w3 and w4 are two weight values. The parameter NL refers to the number of buses that are not being observed twice by the PMUs placement and S is the measurement redundancy used when considering the single PMU loss.…”
Section: Single Pmu Lossmentioning
confidence: 99%
“…The integer linear programming (ILP) method is widely used for solving the OPP problem [5]- [8] since it is capable of solving the OPP problem in a very short time. The exhaustive search (ES) method [9]- [11] and heuristic algorithms such as simulated annealing (SA) [12], genetic algorithm (GA) [13], [14], firefly algorithm (FA) [15], tabu search [16], differential evolution (DE) [17], [18], and particle swarm optimization (PSO) through a binary variant called binary PSO (BPSO) [19]- [25] have shown that they are also capable of finding the optimal placement of PMUs. In these existing studies, many constrained factors such as the effect of the zero-injection bus (ZIB), conventional measurement, a single PMU loss, line outage and PMU's channel limits are considered while solving the OPP problem.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear constraints were formed when considering an adjacent zero-injection bus based on the hybrid topology transformation. Differential evolution (DE) optimization was adopted by Al-Mohammed et al [21] to solve the OPP problem. Chakrabarti and Kyriakides [22] used exhaustive search (ES) algorithm where the authors claimed it gave better results than the method used by Xu and Abur [13] based on the uniform measurement redundancies obtained in the results.…”
Section: Introductionmentioning
confidence: 99%